Quantitative and specific recovery of natural organic and mineral sulfur for (multi-)isotope analysis. (August 2020) - Jovovic, I.; Grossi, V.; Adam, P.; Simon, L.; Antheaume, I.; Gelin, F.; Ader, M.; Cartigny, P.
Highlights: Stepwise chemical procedure for multi-sulfur species recovery from a single sample. (Multi-)isotope analysis of purified sulfur species. New insights into sulfur biogeochemical cycle from multi S-pools analysis. Abstract: Deciphering the role of sulfur in biogeochemical cycles strongly relies on its stable isotope composition, which ultimately depends on the ability to quantitatively recover different sulfur species from geological samples. For decades most studies have been restricted to the 34 S/ 32 S composition of bulk samples, using simple methods based on the analysis of SO2 released by sample combustion combined to mass spectrometry. The wet chemistry procedures required to selectively extract specific sulfur species were generally avoided due to their tediousness and inefficiency for some complex matrices, especially when targeting organic sulfur. With the recent advent of multi-isotope studies (investigating the minor sulfur stable isotopes 33 S and 36 S) which rely either on the analysis of sulfur as SF6, or on the use of secondary ion or multi-collector inductively coupled plasma mass spectrometry, wet chemistry-based preparation procedures were brought back to the stage with a renewed interest in developing procedures better adapted to the investigation of specific sulfur species. Here we propose a new stepwise chemical procedure for the quantitative recovery and multi-isotope analysis of organic sulfur from both solvent soluble (total lipid extract) and insoluble (kerogen) fractions, based on a wet oxidation by sodium hypochlorite. This procedure also allows the multi-isotope analysis of inorganic sulfur species (elemental sulfur, sulfates and sulfides) in the same sample. Its application to different well-known petroleum source rocks and to an oil demonstrates its relevance for disentangling the interactions between the different sulfur pools and for shedding new light on the sulfur biogeochemical cycle.